INVESTIGATION OF THE EFFECTS OF ATTITUDE AND MOTIVATION ON ACADEMIC SUCCESS WITH STRUCTURAL EQUALITY MODELING - Aksoğan, Mustafa; Özdemir, Oğuzhan (Bilgi Yolu Eğitim Kültür ve Sosyal Araştırmalar Merkezi: BİLSAM, 2022)
The aim of this study is to determine the effect of high school students’ attitudes and motivations towards mathematics course on their academic achievement. For this purpose, 250 students studying at different grade levels in three different high schools operating in the province of Malatya were reached. As data collection tools, the attitude scale consisting of 22 items (Onal, 2013) and the motivation scale consisting of 12 items (Kesici, 2018) were used. For the academic achievement scores of the students, the report cards in the spring semester of the 2018-2019 academic year were used. The data were analyzed by statistical programs. Path analysis, one of the types of structural equation modeling, was used to test the model developed within the scope of the relevant literature. With the model used, the effects of students’ attitudes and motivations towards the mathematics lesson on their academic success in the mathematics lesson were examined. According to the research results; It was determined that attitudes and motivations towards mathematics course have a positive and strong effect on academic achievement. Accordingly, the increase in attitude and motivation increases academic achievement, while the decrease in attitude and motivation causes academic success to decrease.

Bu araştırmanın amacı lise öğrencilerinin matematik dersine karşı tutum ve motivasyonlarının akademik başarıları üzerindeki etkisini belirlemektir. Bu amaç doğrultusunda Malatya ilinde faaliyet gösteren üç farklı lisede farklı sınıf düzeylerinde öğrenim gören 250 öğrenciye ulaşılmıştır. Veri toplama aracı olarak 22 maddeden oluşan tutum ölçeği (Önal, 2013) ve 12 maddeden oluşan motivasyon ölçeği (Kesici, 2018) kullanılmıştır. Öğrencilerin akademik başarı puanları için ise 2018-2019 öğretim yılı bahar dönemindeki karne notları kullanılmıştır. Veriler istatistik programları ile analiz edilmiştir. İlgili literatür kapsamında geliştirilen modeli test etmek için yapısal eşitlik modellemesi türlerinden yol analizi kullanılmıştır. Kullanılan model ile öğrencilerin matematik dersine karşına tutumları ve motivasyonlarının, matematik dersindeki akademik başarıları üzerindeki etkileri incelenmiştir. Araştırma sonuçlarına göre; matematik dersine karşı tutum ve motivasyonların akademik başarı üzerinde pozitif ve güçlü bir etkisi olduğu belirlenmiştir. Buna göre tutum ve motivasyonun artması akademik başarıyı arttırırken, tutum ve motivasyondaki azalma akademik başarının düşmesine neden olmaktadır.
TUTUM VE MOTİVASYONUN AKADEMİK BAŞARI ÜZERİNDEKİ ETKİLERİNİN YAPISAL EŞİTLİK MODELLEMESİ İLE İNCELENMESİ